Skybus Airlines: the spectacular failure of an excellent idea - Alvarez, Sharon (Henry Stewart Talks, 2017)
This case study describes the early success and rapid decline of Skybus, a no-frills airline that defined a market opening and created a robust business model, only to be brought down by skyrocketing oil prices and the financial crisis. It examines how the company followed the rules on how to prepare a successful launch yet failed in spite of everything.